Neo-Fisherian monetary policy - Mika Kortelainen (Bank of Finland, 2017)
According to the Neo-Fisherian Hypothesis a nominal policy rate increase leads to an in-crease in the rate of inflation also in the short-run and the effects of Neo-Fisherian forward guidance on inflation and output are small. These results are obtained by assuming that the nominal interest rate is unresponsive to the output gap and inflation at least temporarily and that an arbitrary assumption that a backward stable perfect foresight solution is selected among a continuum of perfect foresight equilibria is valid. The result that nominal policy rates can move inflation in the same direction is at odds with monetary theory and practice.
URN:NBN:fi:bof-201708011448
Keywords: E47; E52; E61; 330; Neo-Fisherian Hypothesis; Monetary Policy; Liquidity